Fuzzy Logic Implementation to Control Temperature and Humidity in a Bread Proofing Machine - Aulia Ullah; Oktaf Brillian Kharisma; Imam Santoso (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
Factors that need to be considered of producing good quality bread are raw materials, balance formulas (recipes) and production processes. The bread dough that cannot proof perfectly has become a problem in the process of bread production. Therefore, the temperature and humidity of the room must be controlled at a certain temperature range. The solution of this problem is proposing a controller that uses Fuzzy logic to control temperature and humidity in the bread examination room. A bread proofing machine is added a controller such as evaporator that it is can controlled the temperatur and humidity automatically. The heat and steam produced are regulated using a Fuzzy logic algorithm embedded in the microcontroller with a predetermined set point of temperature and humidity is 35 oC and 80%. The test is done by determining the percentage error from the temperature and humidity test results, that is when the machine is free of load obtained the percentage error to set points is 0,429 % and 0,937 %. While the engine is loaded. It gives the results are 0,024 % and 0,015%. The results of this test prove that controlling temperature and humidity in a bread proofing machine using Fuzzy logic can provide good results compared to conventional controllers. as a result, the bread mixture can expand uniformly.